Evaluasi Ketersediaan Energi dan Zat Gizi Makro, Tingkat Kepuasan, serta Sisa Makanan pada SD Khazanah Ilmu Sidoarjo: Evaluation Of Energy, Macronutrient Availability, Satisfaction Level, and Food Waste At Khazanah Ilmu Elementary School Sidoarjo - Nabila, Handini Fatihatun; Ruhana, Amalia (JURNAL GIZI DAN KESEHATAN, 2025)
Primary school-aged children are in a phase of rapid growth and development that requires optimal intake of energy and macronutrients. Efforts to meet children's intake needs in full day school can be done by providing lunch at school. However, often the food provided by schools does not meet the contribution of daily energy and nutrient needs and has low acceptability in children. The purpose of this study was to evaluate the availability of energy and macronutrients, satisfaction level, and food waste provided by school catering. The purpose of this study was to describe the availability of macronutrients against the daily RDA, the level of student satisfaction, and student food waste on the menu provided by the catering of SD Khazanah Ilmu Sidoarjo. This study is a quantitative descriptive study using a cross sectional approach. The population of this study was 55 students from grades 1-6 who participated in school catering. SD Khazanah Ilmu uses the services of 2 caterers, namely catering A and catering B. The results of the study showed that the menu provided by catering A of Khazanah Ilmu Elementary School had an average energy of 509 kcal, 21.3 grams of protein, 12.7 grams of fat, and 75.9 grams of carbohydrates. In catering B, the average availability of energy was 426 kcal, protein 15.1 grams, fat 13.3 grams, and carbohydrates 59.1 grams. The average level of student satisfaction from both caterers is classified in the satisfied category. The average food waste in catering A is 21% and in catering B is 21% and in catering B by 18.8%. Catering are expected to increase the availability of nutrients and minimize food waste by providing menus according to portions. ABSTRAK Anak usia sekolah dasar berada pada fase pertumbuhan dan perkembangan yang pesat sehingga membutuhkan asupan energi dan zat gizi makro yang optimal. Upaya untuk memenuhi kebutuhan asupan anak pada full day school dapat dilakukan dengan menyediakan makan siang di sekolah. Namun, seringkali makanan yang disediakan oleh sekolah belum memenuhi kontribusi kebutuhan harian energi dan zat gizi serta memiliki daya terima yang rendah pada anak. Tujuan penelitian ini adalah untuk mengevaluasi ketersediaan energi dan zat gizi makro, tingkat kepuasan, serta sisa makanan yang disediakan oleh katering sekolah. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan menggunakan pendekatan cross sectional. Populasi penelitian ini yaitu sebanyak 55 siswa mulai dari kelas 1- 6 SD yang mengikuti katering sekolah. SD Khazanah Ilmu menggunakan 2 jasa katering, yaitu katering A dan katering B. Hasil dari penelitian didapatkan menu yang disediakan oleh katering A sekolah SD Khazanah Ilmu memiliki rata-rata energi sebesar 509 kkal, protein 21,3 gram, lemak 12,7 gram, dan karbohidrat 75,9 gram. Pada katering B rata-rata ketersediaan energi sebesar 426 kkal, protein 15,1 gram, lemak 13,3 gram, dan karbohidrat 59,1 gram. Rata-rata tingkat kepuasan siswa dari kedua katering tergolong dalam kategori puas. Rata- rata sisa makanan pada katering A yaitu 21% dan pada katering B sebesar 18,8%. Pihak katering diharapkan dapat meningkatkan ketersediaan zat gizi dan meminimalisir adanya sisa makanan dengan menyediakan menu sesuai porsi.